Occlusal vertical dimension: Effect on esthetic norms at smile - Aayesha Razzaque; Shalini Joshi; Sunil Dhaded; Chandrashekar Sajjan; Priyanka Konin; T Subashani (Wolters Kluwer Medknow Publications, 2018)
Background and Objectives: The restorative and esthetic needs for the complete mouth rehabilitation patient frequently require an increase in occlusal vertical dimension (OVD), in whom there would be tooth loss or attrition in existing teeth, decreased OVD, or opposing teeth supraeruption. The effect of increasing OVD for restorative purpose and esthetic norms while smiling is not well understood; hence, the purpose of this study is to evaluate the effect of those norms at smile. Methods: Eighty patients (40 males and 40 females) were selected from the student population of AME's Dental College, Raichur, between the age groups 21 and 30 years, and occlusal registrations of 2, 4, 6, and 8 mm in thickness for each individual were fabricated from the articulated casts. Posed smile images at OVD +0, +2, +4, +6, and +8 were taken with a digital single lens reflex (DSLR) camera and evaluated using AutoCAD software. Results: In this study, it was found that with an increase in OVD, the interlabial gap height, incisal edge to lower lip distance, and display zone area were increased statistically significantly (P < 0.05) in both male and female patients, whereas the smile index was decreased significantly (P < 0.05). No significant changes were observed in the intercommissural width and incisal edge to the upper lip distance in both male and female patients. Conclusion: There is obvious effect of aesthetic norms such as the vertical distance between the incisal edge to upper lip, vertical distance between incisal edge-lower lips, interlabialgap height, intercommissural width, internal display zone area, and smile index in both male and female patients. The obtained values can serve as guide for esthetic rehabilitation of patients.